Data and information management for the monitoring of biodiversity in Alberta. (27th August 2015) - Sólymos, Péter; Morrison, Shawn F.; Kariyeva, Jahan; Schieck, Jim; Haughland, Diane L.; Azeria, Ermias T.; Cobb, Tyler; Hinchliffe, Robert; Kittson, Jillian; Mcintosh, Anne C. S.; Narwani, Tara; Pierossi, Paola; et al.
ABSTRACT The Alberta Biodiversity Monitoring Institute (ABMI) monitors large‐scale responses of biodiversity to environmental change in Alberta, Canada, based on standardized and ongoing data collection. In this case study, we show that such a standardized monitoring system has many data management challenges. In the almost 20 years since the conception of the Institute, we have identified 4 key characteristics that are required for large‐scale, long‐term biodiversity monitoring programs to be operational: 1) data must be publicly accessible; 2) methods and terminology must be standardized to facilitate consistency around data and information collection, analysis, and reporting; 3) the information system must be flexible so that components can be modified or added without compromising the functionality of the other components or the whole system; and 4) the system must be scalable so that it can support input, storage, and retrieval as data load increases. These characteristics are important to ensure that the products and tools generated from our monitoring program can support management at large spatial scales in the complex socio‐ecological system of Alberta. © 2015 The Wildlife Society.